LNG and UK energy security - Marshall Hall (The Oxford Institute for Energy Studies, 2023)
This paper discusses the supply of regasified LNG to the wholesale gas market and its contribution to UK energy security in the context of the fundamental changes to European gas price-formation in the last decade. It examines the three parts of the LNG supply chain; the functioning of the global LNG market, the capacity holdings and commercial operations at the UK's three regas terminals and, thirdly, access to entry capacity on the regulated National Transmission System. The UK gas price crisis in Europe in 2021-22 revealed not only the flexibility and liquidity of LNG markets and the critical new role that the market for spot uncontracted LNG now plays in NBP and TTF price-determination but also unexpected constraints on the NTS. UK gas supply is diverse but unbalanced in its lack of seasonal storage capacity and dependence on attracting LNG to meet peak winter demand. Regasified LNG now provides the main source of flexible supply to the NBP market in winter, as demonstrated in the protracted cold spell in December 2022, but UK shippers are restricted in their ability to exploit periods of LNG market weakness to build inventories for winter. The consequence is a disproportionate financial exposure of UK energy consumers to the price of uncontracted LNG in the winter months. The gas price crisis of 2021-22 highlighted the UK's favourable access to LNG but also some weaknesses in the existing approach to energy security and current regulatory arrangements. A thorough post-crisis review of UK energy security and affordability in 2023 would be a timely commitment by the new DESNZ. The UK has embarked on another wave of investment in regas and NTS capacity to accommodate LNG imports just as it faces more intense competition for LNG supply from both Asian and new European markets. In order to ensure that the UK remains competitive within Europe, DESNZ and Ofgem should seek to address a number of issues; the high cost of NTS entry capacity, the stability and fairness of capacity charging, NBP market liquidity, gas quality regulations and capacity congestion management.
Keywords: 330; energy security; LNG; NBP price-formation; regas terminals; Russia-Ukraine Crisis; UK gas supply